Analisis Determinan Pendapatan Pelaku UMKM Di Kabupaten Karawang - lukita, Carolyn; Liana, Siska; Ramdan, Nurul Amalia (LPPM POLITEKNIK LP3I BANDUNG, 2025)
This study aims to examine the effect of financial technology, number of workers, business capital, accounting understanding, and age of business actors on MSME income in Karawang Regency. The data used is primary quantitative data, obtained by survey with owners and managers of MSMEs in Karawang district as the population. The sample selection technique with simple random sampling, a total of 105 respondents were managed using SPSS. The results of this study indicate that financial technology, the number of workers, and business capital have a significant effect on MSME income in Karawang Regency. Meanwhile, the variables of accounting understanding and age of business actors have no effect on MSME income in Karawang Regency.